The integration of Soft Skills in Higher Education: Investigating the Perception of 40 Moroccan Employees - Abdelhafid Jabri (Firenze University Press, 2023)
This article sets out to explore the prospects of integrating soft skills in Moroccan higher education, with particular emphasis on Mohammed I University. Once Morocco expressed its desire to adopt a soft-skill-based system in 2021, scholars have underscored the benefits of equipping university students with the necessary skills for their employability. This study is part of this growing attention to the Moroccan experience. Building on the perceptions of twenty English language teachers and twenty public sector employees who graduated from Mohammed I university, it investigates the following queries: Do soft skills play a key role in the professional life of those university graduates? Which soft skills should be more emphasized in higher education? And how can they be integrated in the university curriculum? Results suggest that while the two groups of participants had different views about which soft skills to be more emphasized, both agree that extra-curricular activities and ongoing professor training are key to their integration in higher education provided that due attention is given to social interaction. This study can bring new insights into the real needs of the Moroccan job market.   L'integrazione di soft skills nell'Istruzione Superiore: investigare la percezione di 40 lavoratori marocchini. Questo articolo si propone di esplorare le prospettive di integrazione delle soft skills nell'istruzione superiore marocchina, con un focus sull'Università Mohammed I. Dopo che il Marocco ha espresso il desiderio di adottare un sistema basato sulle soft skills nel 2021, studiosi hanno sottolineando i vantaggi di dotare gli studenti universitari delle competenze necessarie per la loro occupabilità. Il presente studio si inserisce in questa crescente attenzione all'esperienza marocchina. Basato sulle percezioni di 20 insegnanti di lingua inglese e 20 impiegati del settore pubblico laureati all'Università Mohammed I, indaga le seguenti domande: Le soft skills giocano un ruolo fondamentale nella vita professionale di questi laureati? Quali soft skills dovrebbero essere maggiormente enfatizzate nell'istruzione superiore? E come possono essere integrate nel curriculum universitario? I risultati suggeriscono che, sebbene i due gruppi di partecipanti abbiano opinioni diverse su quali soft skills dovrebbero essere maggiormente enfatizzate, entrambi concordano sul fatto che le attività extra-curriculari e la formazione continua per i professori sono fondamentali per la loro integrazione nell'istruzione superiore, a condizione che si presti la dovuta attenzione all'interazione sociale. Questo studio può portare nuovi spunti di riflessione sulle reali esigenze dei docenti.